STRATEGIC PLANNING IN INDUSTRIAL ENTERPRISES - Yusupxodjaeva Gulchexra Baxadirxodjaevna; Kholmukhamedova Feruza Areslanbekovna (American Journals, 2024)
The article is devoted to the issues of strategic planning in industrial enterprises, including its role in improving efficiency and competitiveness in a market economy. The main stages and methods of strategy development, features of choosing the optimal strategy and its adaptation to changing environmental conditions are considered. Special attention is paid to the assessment of economic feasibility and risks in strategic planning. The paper also presents theoretical foundations, methods and approaches that can be applied to implement strategic planning in enterprises of Uzbekistan.
Keywords: Production potential, innovative economy, industrial enterprises, strategic development, use assessment, global financial crisis, production growth, investment resources, competitiveness, economic growth, material resources, labor resources, technological potential, managerial potential.